2021
DOI: 10.21037/jtd-20-3072
|View full text |Cite
|
Sign up to set email alerts
|

Does sarcopenia affect postoperative short- and long-term outcomes in patients with lung cancer?—a systematic review and meta-analysis

Abstract: Background: Lung cancer patients frequently suffer from sarcopenia, and reports on the association of resectable lung cancer and their postoperative outcomes are increasing. Information on whether sarcopenia has any impact on short-and long-term postoperative outcomes in patients surgically treated for nonsmall cell lung cancer remains insufficient. Furthermore, reports vary regarding the pathological stage, surgical procedure, diagnostic tool of sarcopenia, cut-off value, prognosis, and postoperative complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…The research team of eight [ 18 , 20 – 25 , 27 ] reviews was based in Asian countries, five [ 16 , 17 , 26 , 28 , 29 ] in European countries, and one [ 19 ] in the United States of America. Eight [ 16 21 , 24 , 29 ] reviews focused on malignancies of pulmonary origin, with four [ 18 , 21 , 24 , 29 ] solely examining NSCLC and four [ 16 , 17 , 19 , 20 ] encompassing all lung cancers. The remaining six [ 22 , 23 , 25 28 ] reviews incorporated tumors from multiple locations and dedicated a portion to lung cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research team of eight [ 18 , 20 – 25 , 27 ] reviews was based in Asian countries, five [ 16 , 17 , 26 , 28 , 29 ] in European countries, and one [ 19 ] in the United States of America. Eight [ 16 21 , 24 , 29 ] reviews focused on malignancies of pulmonary origin, with four [ 18 , 21 , 24 , 29 ] solely examining NSCLC and four [ 16 , 17 , 19 , 20 ] encompassing all lung cancers. The remaining six [ 22 , 23 , 25 28 ] reviews incorporated tumors from multiple locations and dedicated a portion to lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…According to the critical appraisal using AMSTAR2, one review [ 20 ] had high, nine had low [ 17 , 18 , 21 23 , 25 , 27 29 ], and four [ 16 , 17 , 19 , 24 , 26 ] had critically low evidence quality. Common methodological problems were lack of prior protocol registration (only registered in two reviews [ 27 , 29 ]), not employing a comprehensive search strategy (three reviews [ 19 , 24 , 26 ] used only PubMed for literature search and 12 [ 16 19 , 22 29 ] did not consider trial registries), and not providing sufficient information on the excluded studies (only recorded in three reviews [ 16 , 20 , 25 ]). Seven reviews [ 18 , 19 , 22 24 , 26 , 28 ] did not elaborate on duplicate study selection, and seven [ 16 , 17 , 22 , 23 , 26 28 ] did not show independent data extraction by two authors.…”
Section: Resultsmentioning
confidence: 99%
“…We could not determine whether sarcopenia directly affected cancer recurrence using OS or DFS, because decreases in OS or DFS are not only attributable to lung cancer death/recurrence, but also to deaths from other diseases. Indeed, sarcopenia itself is a poor prognostic factor, because the loss of muscle mass and strength results in physical disability and death [ 10 , 23 ]. Second, we focused on lobectomy as the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…First, sarcopenia itself is generally accepted to confer poor prognosis. Even if the cancer is completely cured through surgery, there is loss of skeletal muscle mass and strength, resulting in physical disability and death [ 10 ]. Second, sarcopenia may also contribute to the risk of cancer recurrence [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that sarcopenia has an impact on the prognosis of various cancers. The survival rate of patients with sarcopenia is signi cantly lower than that of patients with esophageal cancer (Jin et al, 2021), colorectal cancer (Xie et al, 2021), pancreatic cancer (Cho et al, 2021), lung cancer (Kawaguchi et al, 2021) without sarcopenia. In general, sarcopenia plays an important role in the prognosis of cancer patients.…”
Section: Introductionmentioning
confidence: 99%